THựC NGHIệM NUÔI TÔM CàNG XANH (MACROBRACHIUM ROSENBERGII DE MAN, 1897) VớI MậT Độ KHáC NHAU TRONG AO ĐấT - Tuấn, Nguyễn Anh; Long, Dương Nhựt; Việt, Lê Quốc (Tạp chí Khoa học Đại học Cần Thơ, 2004)
Abstract The experiment on giant freshwater prawn (Macrobrachium rosenbergii) culture was carried-out in Long An village, Long Ho District and Long Phu village, Tam Binh District,VinhLongProvincefrom May to November, 2003. Two different stocking densities of 8 (treatment 1) and 12 juvenile/m2 (treatment 2) were randomly designed in six ponds of 1000 - 1200 m2 /each. The initial size of prawns were 0.46 - 0.71 g, 3.12 - 3.43 cm. Prawns were fed by 50 % pellet feed (32 ? 36 % of protein) and 50 % freshwater trash fish. Feeding rate and feeding frequency were 3 ? 7 % /total body weight /day and two times per day, respectively. The results showed that the water quality in cultured system such as water temperature, water pH, transparency, oxygen, N-NH4+, N-NO2- and H2S were acceptable values for the freshwater prawn growing and developing. The survival rate of freshwater prawn in earthen ponds obtained in treatment 1 (39.8 ± 2.2 %) was not significantly higher (P > 0.05) than those in treatment 2 (34.9 ± 2.2 %) after 180 days. The growth rate of prawn obtained in treatment 1 (0.22 g /day) was significantly higher (P < 0.05) than that in treatment 2 (0.18 g/day). The highest yield of freshwater prawn trial in earthen ponds was 1,130 kg/ha. Freshwater prawn culture at 8 juvenile/m2 in earthen ponds could be utilized for improving farmer?s income in theMekongDelta. Key words: Freshwater prawn, Stocking density, Feeding rate Title: Experimental culture of giant freshwater prawn (Macrobrachium Rosenbergii De Man, 1897 ) at different stocking densities in earthen ponds